Respostas
respondido por:
4
(x + 3)(2x - 4) =0
2x² - 4x + 6x - 12 = 0
2x² + 2x - 12 = 0 (÷2)
x² + x - 6 = 0
Δ = (1)² - 4(1)(-6)
Δ = 1 + 24 = 25
√Δ = 5
x1 = (-1 + 5)/2 = 4/2 = 2
x2 = (-1 - 5)/2 = -6/2 = -3
Resposta: ={x ∈ R / x= 2 ou x = -3}
Espero ter ajudado.
2x² - 4x + 6x - 12 = 0
2x² + 2x - 12 = 0 (÷2)
x² + x - 6 = 0
Δ = (1)² - 4(1)(-6)
Δ = 1 + 24 = 25
√Δ = 5
x1 = (-1 + 5)/2 = 4/2 = 2
x2 = (-1 - 5)/2 = -6/2 = -3
Resposta: ={x ∈ R / x= 2 ou x = -3}
Espero ter ajudado.
respondido por:
3
(x +3 ) (2x - 4)=0
==> x + 3 = 0 ==> x' = - 3 ==> 2x - 4 = 0 ==> 2x = 4 ==> x = 4/2 ==> x = 2 ==> S = {-3,2}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás